Synthesis, Molecular Structure, and Water Electrolysis Performance of TiO2-Supported Raney-IrOx Nanoparticles for the Acidic Oxygen Evolution Reaction - Kang, Jiaqi; Wang, Xingli; Möhle, Sebastian; Farhoosh, Shima; Kovács, Miklós Márton; Schmidt, Johannes; Liang, Liang; Kroschel, Matthias; Selve, Sören; Haumann, Michael; Dworschak, Dominik; Dau, Holger; et al. (ACS Catalysis, 2025)
Developing low-cost, highly active, and stable catalysts for the acidic oxygen evolution reaction (OER) at the proton exchange membrane (PEM) water electrolyzer anodes remains a scientific priority. Reducing the iridium loading while increasing the intrinsic activity of the catalysts is essential for cost-effective hydrogen production. Here, we address a family of TiO2-supported Raney-IrOx catalysts with low iridium loading and high activity in single-cell PEM water electrolyzer anode environments. A controlled Raney-type Ni leaching process of pristine, supported IrNi alloy phases forms crystalline IrOx nanoparticles (NPs) featuring metallic Ir-rich cores surrounded by more amorphous IrOx surfaces. This structure is shown to be conducive to catalytic activity and the suppression of membrane poisoning due to Ni degradation. The trace amounts of Ni remaining after leaching in the IrOx NPs result in heterogeneous crystal structure and induce local lattice strain. Further, we synthetically strike a balance between conductivity and activity and succeed to narrow down the notorious large performance gap between liquid electrolyte rotating disk electrodes (RDEs) and single-cell membrane electrode assembly (MEA) electrolyzer measurements. OER stability numbers (S-numbers) of the identified Raney-IrOx anode catalysts surpass commercial IrO2 catalysts, confirming the stability of these catalysts. The PEM electrolyzer tests reveal that Raney-IrOx anodes achieve 3 A cm-2 at 1.8 V with a low geometric Ir loading of ca. 0.3 mgIr cm-2, meeting the technically important power specific Ir utilization target of 0.05 gIr/kW.
CRIS-Team Scopus Importer:2025-04-01
Keywords: electrocatalysis; electrolysis; iridium; oxygen evolution reaction; PEM water electrolyzer